The rich demystified: A reply to Bach, Corneo, and Steiner (2008) - Martin Jacob; Rainer Niemann; Martin Weiss (Arbeitskreis Quantitative Steuerlehre (arqus), 2008)
The contribution Bach, Corneo and Steiner (2008) has argued that "the rich" do not pay taxes adequately in relation to their income, finding, for instance, an effective tax rate of only 38.1% for the 0.001% fractile of German income taxpayers in 2001. This result contrasts sharply with the legislated top marginal income tax rate of 48.5%. We subject the results contained in Bach, Corneo and Steiner (2008) to a rigorous analysis: We find major flaws and inconsistencies with regard to methodology, i.e. the omission of corporate taxes and inter-temporal aspects of taxation. Restating basic rules for the measurement of effective tax rates, we provide values for what we term the "comprehensive nominal tax rate" (CNTR) and show that the headline result in Bach, Corneo and Steiner (2008) of 38.1% is underestimated by over 12 percentage points. As an important distributional result, the CNTR increases with increasing taxable income.
Keywords: D31; H00; H24; H25; 330; Top Incomes; Income Taxation; Taxing the Rich; Comprehensive Tax Burden